Teacher perception of self-concept and academic performance of adolescents with temporary special educational needs (Revista INTEREDU11, 2023)
The main objective of this research has been to know the perception of teachers about academic self-concept and school performance in adolescent students with Temporary Special Educational Needs (TSEN). This study has been carried out through a qualitative approach and a cross-sectional design, by using a semi-structured interview over 8 professionals of both, regular and differential education from four public and private educational institutions in Osorno. Among the main results, it has been found that most members of the teaching staff have stated that they perceive a rather low academic self-concept in their students with TSEN, with a tendency to change, to be unstable and fickle over time, and depending on subjects which they reckon to be influenced by both, personal, and environmental factors. Regarding academic performance, professionals have pointed out that this may vary over time, influenced by both extrinsic and intrinsic factors. The faculty have also highlighted a bidirectional relationship between academic self-concept and the academic performance upon such students. Finally, teachers have delivered a series of suggestions to enhance these variables either at the classroom level or at the institutional level.
Keywords: Self-concept; special education; educational needs; education professionals; school performance